LncRNA PCAT1 promotes metastasis of endometrial carcinoma through epigenetical downregulation of E-cadherin associated with methyltransferase EZH2 - Zhang, Chunhua; Shao, Shasha; Zhang, Yujian; Wang, Liyang; Liu, Jianzhong; Fang, Fang; Li, Peiquan; Wang, Bo (Life sciences (1973), 2020)
More than 140 thousands of women suffer from endometrial carcinoma in the worldwide, and over 40 thousand of the patients die before and after in surgery and chemoradiotherapy because of its metastasis. However, its molecular mechanism is much less known compared to other cancers. In this study, we demonstrated that long non-coding RNA PCAT1 is dramatically increased in the tissues and plasma from endometrial carcinoma (EC) (n = 100, all p < 0.001) controlled by its paracancerous tissue, and cell lines including RL-952, HEC-1-B, KLE, Ishikawa, and AN3CA compared to the cells from normal endometrium (all p < 0.001). When lncRNA PCAT1 was knocked-down, the KLE and AN3CA cells exhibited slow capability on proliferation and colony formation in vitro. With the silence of lncRNA PCAT1, the cells were markedly inhibited on migration and invasion in vitro (all p < 0.001), which were confirmed on the EC patient subjects. When expressions of lncRNA PCAT1 were interfered in the cells, expressions of E-cadherin but not N-cadherin and Vimentin were significantly promoted with a strong up-regulation accompanied by nearly completed recoveries on migration and invasion (all p < 0.001). In order to analyze the association of lncRNA PCAT1 and E-cadherin, we silenced the expressions of both genes and unveiled that EC migration and invasion were significantly congested (all p < 0.001). Importantly, we found that the E-cadherin down-regulation caused by lncRNA PCAT1 associates with histone methyltransferase EZH2. When over-expression of EZH2 was applied in the PCAT1 silenced cells, the expression of E-cadherin experienced significant decrease in the cell lines. Reversely, when expression of EZH2 was annulled in the PCAT1 silenced cells, the expression of E-cadherin was significantly boosted in the cells (all p < 0.001). Furthermore, the interaction of lncRNA PCAT1 and EZH2 were approved with immunoprecipitation. Our data demonstrated that the methyltransferase EZH2 related up-regulation of lncRNA PCAT1 along with down-regulation of E-cadherin could be essential in oncogenesis of endometrial carcinoma in both EC cells and patient subjects. These compact data suggest that combination of lncRNA PCAT1, EZH2 and E-cadherin could provide valued information for efficient EC diagnostics, which would propose a potential target for EC treatment with EZH2i on methyltransferation.